A low cost solid state pulsed system for ultrasonic velocity and absorption measurement - AGNIHOTRI, P. K.; ADGAONKAR, C. S.; BEDARE, C. Y. (Archives of Acoustics, 1987)
An instrument is described to generate and detect pulsed ultrasonics. The instrument should be useful for ultrasonic measurements in gases for teaching laboratories and for research purpose because of its low cost and ease of construction.The instrument is tested for ultrasonic wave velocity and absorption in air at frequency 40 kHz and at atmospheric pressure. The results are very much satisfactory.